Secular Spirituality and the Hermeneutics of Ontological Gratitude - Colledge, Richard J. (Sophia, 2013)
In his 2010 article, ‘Secular Spirituality and the Logic of Giving Thanks’, John Bishop recalls a striking theme in a recent address by Richard Dawkins in which he appeared to enthusiastically endorse the appropriateness of a ‘naturalised spirituality’ that involved ‘existential gratitude’, and this led him to investigate the notion of a naturalised or secular spirituality with particular reference to Robert Solomon’s Spirituality for the Skeptic (2002). This essay looks to pick up on Bishop’s engagements with both Dawkins and Solomon, but to extend the conversation well beyond them in order to defend the credibility and integrity of secular spirituality in its movement of ontological gratitude. In this way it looks to offer a first sketch of what might be termed a ‘hermeneutics of ontological gratitude’. To this end – and via a distinction between gratitude for existence and life – the essay considers Dawkins’ argument and Solomon’s work in further detail, before turning to consider various other perspectives on the problem including Kenneth Schmitz’s existential Thomist notion of ontological contingency, Hannah Arendt’s concept of primary natality, and Emmanuel Levinas’ sketch of the self in its interiority and economy. My claim is that any serious naturalistic spirituality needs to take into account not only a gratitude for one’s existence per se, but for the whole context of individual and collective being.